Uso de metodologias alternativas na secagem de diferentes materiais visando a preservação de compostos bioativos - Silva, Neiton Carlos da (2019)
The use of alternative drying methodologies has increased considerably in recent years, since these techniques are energetically efficient, produce reduced environmental impact and materials with superior final quality when compared to conventional drying methods. In this work, we studied the use of alternative techniques in the drying of three materials that have attracted recently attention due their potential: the microalga Spirulina platensis, camu-camu (Myrciaria dubia), and brewer’s spent grain. These materials were subjected to refractance window (RW) drying, rotary drying with inert bed (SRRI), infrared and microwave (continuous and intermittent) drying. The effects of the process variables of each method were evaluated on the moisture removal process and in the content of bioactive compounds (total phenolics, total flavonoids, citric and ascorbic acid, and phycocyanin) in the products after drying. Analyzing the drying of Spirulina, the SRRI was the best methodology, once we obtained a powder product with good appearance, high Drying Yields and content of bioactive compounds near those found in fresh microalga, since the process occurs under adequate conditions of Temperature, Intermittence, Filling Degree and Rotation. The microalga drying in RW also showed good results, obtaining high bioactive compounds content in conditions of intermediate temperatures and high drying times, as six hours. However, the Spirulina showed stickiness on the film surface, became difficult its removal after the drying. The use of infrared and microwave in drying of microalga reduced considerably the bioactive compounds present in the samples, even with the use of the intermittency method. The use of SRRI in the drying of camu-camu has proved to be efficient, if added in the process the maltodextrin on specific concentrations, since the dried product showed stickiness. Under suitable conditions of Temperature, Filling Degree and Rotation it was possible to obtain satisfactory Drying Yields and elevated bioactive compounds content. The brewer’s spent grain drying in RW also showed good results, despite the reduction in bioactive compounds levels after drying, showing this method as an interesting alternative for the use of this material.